Persepsi Siswa Terhadap Pelaksanaan Layanan Bimbingan Pribadi - Amronah, Amronah (Universitas Ahmad Dahlan, 2014)
The study aims to reveal the students perception of the implementation of personal guidance services by teacher guidance and counseling in schools. This type of research is quantitative descriptive study. Samples in this study amounted to 105 class XI student of SMK Negeri 1 Yogyakarta taken by using proportional random sampling. Collecting data using questionnaires students perception of the implementation of private tutoring services. Mechanical data analysts use a simple calculation with a grouping of three criteria: good, average and less. The results showed that the students perception of the implementation of private tutoring services as many as 78 (74.3%) in both categories, 27 (25.7%) in the medium category, and 0 (0%) in the poor category. The results of data analysis can be concluded that students perceptions of personal counseling service implementation class XI student of SMK Negeri 1 Yogyakarta with either category. Information from this research can be considered for guidance and counseling teachers in the development of service quality as well as the personal guidance for the development of personal guidance services program for vocational students.